Description of Culture Shock among Papuan Students and Implications for Guidance and Counseling Services - Abdillah, Wahyu; Yendi, Frischa Meivilona; Sukma, Dina; Handayani, Puji Gusri (International Journal of Applied Counseling and Social Sciences, 2023)
Feelings of anxiety and restlessness in students result in an inability to adapt, resulting in culture shock. The inability to adapt affects a person's psychology in problem solving, learning and the individual's habits. This research aims to describe culture shock in the affective, behavioral and cognitive dimensions. This research method uses descriptive quantitative with numbers subject 25 active students from Papua at Padang State University. The results of the research show that the culture shock picture of students from Papua at UNP is in the medium category with an overall percentage of 96%. Based on the research results, the implications that can be provided are, orientation services, information services, individual counseling services, group counseling services using relevant counseling approaches.